Integrated Islamic School Learning Management - Asnawati Asnawati (Proceeding International Seminar of Islamic Studies, 2019)
Integrated Islamic School is one form of educational units that offers the concept of integrating curriculum of religious education and general education in its learning methods as well as emphasizing the integration of cognitive, affective and psychomotor aspects. The concept is also developed in integrating aqliyah, ruhiyah and jasadiyah education, also integrating cooperative involvement between teachers, parents and the community in an effort to foster students' character and competencies Through the concept of cohesiveness, the learning activities are arranged in management based on government regulations as well as the content of the school. The management is arranged in a learning plan, implementation and evaluation document. Learning plan is carried out through discussion by teachers while still guiding the concept of cohesiveness. The form of the planning document is from analyzing the educational calendar that has been adjusted to school calendar and realized by educators with a calendar of subjects. The schedule of the calendar is adjusted to the development of the syllabus that is actually arranged in the lesson plan (RPP). The implementation of learning is adjusted to the scenario of the compiled lesson plan integrated with activities outside the classroom that support the learning material in the form of implementation of the integration of learning material with Islamic values. Learning evaluation becomes a benchmark of success or weakness of the learning process. The results of the learning evaluation activities are informed to parents directly or through social media. Usually what is published is a plus, while the shortage of students is only informed to parents to establish cooperation in improving the students' self-quality.